TINGKAT PENCEMARAN LOGAM BERAT DALAM AIR LAUT DAN SEDIMEN DI PERAIRAN PULAU MUNA, KABAENA, DAN BUTON SULAWESI TENGGARA - Ahmad, Fasmi (UI Scholars Hub, 2009)
The Degree of Heavy Metals Pollution in Seawater and Sediment in the Waters of Muna, Kabaena and Buton Island, Norteast of Sulawesi. Muna, Kabaena, and Buton are islands found in Northeast of Sulawesi. One of them, namely Kabaena Island is island which has high Nickel content. Some of mining industries has explored the Nickel content in this area. Tailing come from mining thrown to the sea, will increase the heavy metals content in seawater and sediment in the waters of that third island, remembering the position of that third island not so far. In order to marine pollution monitoring by heavy metals, Research Center for Oceanography has done some marine research in the waters of that third island in April 2006. The aim of this research is to know the impact of Nickel mining activities to heavy metals content in seawater and sediment in that third waters. Heavy metals monitored is Pb, Cd, Cu, Zn, and Ni. The results showed that the content of heavy metals Pb, Cd, Cu, Zn, and Ni in sea water still in line with the threshold value according to Kep MNLH No. 51, 2004 for sea biotas. The same condition also found in sediment, where the content of Pb, Cd, Cu, Zn, and Ni is low relative, and still in line with heavy metals content found in normal seawater.